L’entrepreneuriat et développement territorial : entre innovation et dynamique locale, étude empirique: Entrepreneurship and territorial development: between innovation and local dynamics, empirical study - Younes FERDJ; Aimad Datoussaid (Journal of North African Economies, 2025)
The problem of this article is to study the key factors that have played an important role in the dynamics of the entrepreneurial process. To understand the question of the paradigm of development of the territories, we have chosen the region of Blida as a case study because this wilaya is located in the heart of the rich agricultural countryside of the Mitidja which served as a springboard for the development of the food industry. The study is based on the results of a statistical survey of a sample of agri-food firms where the questioning focuses on the behavior of entrepreneurs in territorial development (Ferdj, 2019, 2020). This work is part, in theory, of an approach where the following theoretical concepts served as explanatory, analytical and interpretative elements of the survey data. Thus, the analytical exploitation of the survey data allowed us to determine the characteristics and specificities of the creator-innovator entrepreneur according to J. Schumpeter (1912).